(untitled) (Religious dialogue and cooperation, 2022)
The subject matter of this writing is the quality- and ethical expectationstowards Christian educators and the codification problems they pose. Webelievethat the set of expectations towards educators can only be examined to themeritsbyextending our research to the judicial, pedagogical and moral aspects of the issue, whiletaking the international context and historical dimensions of these set of expectationstowards educators, of the certification system of educators and the pedagogue-ethicsinconsideration. In this writing, we are attempting to take a multi- directional approachtothis ample topic, offering several ideological- and research crossroads. We believethattherelationship between law and ethics in (Christian) Europe can be divided in threemaineras. The first one is the era of “submission”, which lasted until Enlightenment. Inthisera,God’s declarations set the rules of ethical conduct without any further written regulations.Following the age of Enlightenment and the emergence of civil states, “submission”wasreplaced by “obedience”. The framework of desirable civil conduct (includingethicalconduct) was defined by states’ legal systems, administrations or police-statelawenforcement agencies. By the late 20th-early 21st centuries, in the era of globalization,the role of the states and the trust vested in their judicial systems have been eroded. Thisresulted in the emergence of bottom-up community regulations of ethical conduct. Thus,with regards to ethical conduct, we can dub our era the era of “responsibility”. Preciselythis is why, implementation and use of ethical sets of rules forced on society withouttheiragreement represents a risk.